2022
DOI: 10.1002/jor.25310
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between metabolites in the synovial fluid and serum: A mouse injury study

Abstract: Osteoarthritis, the most common degenerative joint disease, occurs more frequently in joints that have sustained injury. Currently, osteoarthritis is diagnosed with imaging that finds radiographic changes after the disease has already progressed to multiple tissues. The primary objective of this study was to compare potential metabolomic biomarkers of joint injury between the synovial fluid and serum in a mouse model of post-traumatic osteoarthritis. The secondary objective was to gain insight into the pathoph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“… 30 , 31 Proline, a downstream product of arginine, contributes to collagen synthesis 32 and has also been associated with OA 20 , 31 , 33 , 34 . A prior study found higher concentrations of asparagine, arginine, and proline at day 1 that then decreased by day 8 in a non-invasive mouse ACL tear model 29 , suggesting these amino acids could be protective after injury and might be measured over time to monitor OA development. Similarly, NMR analysis of sheep SF following ACL injury found increased levels of serine and asparagine post-injury compared to non-injured sheep 28 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 30 , 31 Proline, a downstream product of arginine, contributes to collagen synthesis 32 and has also been associated with OA 20 , 31 , 33 , 34 . A prior study found higher concentrations of asparagine, arginine, and proline at day 1 that then decreased by day 8 in a non-invasive mouse ACL tear model 29 , suggesting these amino acids could be protective after injury and might be measured over time to monitor OA development. Similarly, NMR analysis of sheep SF following ACL injury found increased levels of serine and asparagine post-injury compared to non-injured sheep 28 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have applied metabolomics to examine metabolic shifts post-injury in animal models [26][27][28][29] , but no study to date has examined metabolic shifts in human SF induced by different injuries. Here, metabolic phenotypes were generated and differences in pathway regulation between injuries were detected.…”
Section: A Acute Metabolic Responses Post-injury Varies Based On Inju...mentioning
confidence: 99%
“…This study provides excellent baseline data on metabolic effects of these two lifestyle modifications on joint metabolism, as well as how these changes correlate to systemic parameters. A related study compared 2500 serum and synovial fluid metabolites after a single injury in mice and showed both similarities and differences between the two body fluids [21].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Synovial fluid was extracted from the stifle joint immediately following euthanization consistent with our previously published protocol 26 . Briefly, an incision was made anteriorly into the synovium and synovial fluid was collected by adsorption using Melgisorb alginate dressing (Tendra).…”
Section: Profiling the Biological Response Of Joints To Traumatic Injurymentioning
confidence: 99%
“…Since bone is highly cellular and vascularized compared with cartilage, assessing metabolic shifts in synovial fluid is expected to produce data that can help contextualize early bone changes after joint injury. Recent studies find distinct metabolic profiles between injured and sham-injured synovial fluid 7d after joint injury in mouse models 25,26 . However, the relevance of shifts in synovial fluid metabolism in injured versus sham-injured, and contralateral-to-injured soon after joint injury on bone outcomes remains uncertain.…”
Section: Introductionmentioning
confidence: 99%